Static stretching does not alter pre and post-landing muscle activation - Moss Wesley R; Feland J Brent; Hunter Iain; Hopkins J Ty (BMC, 2011)
Abstract Background Static stretching may result in various strength and power deficiencies. Prior research has not determined, however, if static stretching causes a change in muscle activation during a functional task requiring dynamic stability. The purpose of this study was to determine if static stretching has an effect on mean pre and postlanding muscle (vastus medialis VM, vastus lateralis VL, medial hamstring MH, and biceps femoris BF) activity. Methods 26 healthy, physically active subjects were recruited, from which 13 completed a 14-day static stretching regimen for the quadriceps and hamstrings. Using the data from the force plate and EMG readings, a mean of EMG amplitude was calculated for 150 msec before and after landing. Each trial was normalized to an isometric reference position. Means were calculated for the VM, VL, MH, and BF from 5 trials in each session. Measures were collected pre, immediately following the 1st stretching session, and following 2 weeks of stretching. Results A 14-day static stretching regimen resulted in no significant differences in pre or postlanding mean EMG amplitude during a drop landing either acutely or over a 14-day period. Conclusions Static stretching, done acutely or over a 14-day period does not result in measurable differences of mean EMG amplitude during a drop landing. Static stretching may not impede dynamic stability of joints about which stretched muscles cross.